Cover Image. Issue 7 (July 2017) - Loth, Eric; Steele, Adam; Qin, Chao; Ichter, Brian; Selig, Michael S.; Moriarty, Patrick
Abstract : The cover image, by Eric Loth et al., is based on the Research Article Downwind pre‐aligned rotors for extreme‐scale wind turbines, DOI10.1002/we.2092 . Photo Credit: Chao Qin.